A Comparative Study of Biomass and Carbon Stock in Tropical and Temperate Forests of Ilam District in Nepal - Poudel, Animesh; Dahal, Krishna; Joshi, Mohit; Thapa Magar, Sakshi; Kharel, Ripesh (Banko Janakari, 2025)
Quantification of biomass and carbon is imperative in optimizing ecological and low-carbon emission-oriented economic benefits of forestland. This study quantified stock densities of carbon in two distinct forests, viz., tropical and temperate. We selected two Community Forests (CFs) with predominance of Shorea robusta in the tropical and Castanopsis sp. in the temperate region of Ilam district (Chure and Mid-hill). Data were gathered using stratified systematic sampling with a 1% sampling intensity. It was discovered that the overall stock (carbon) in the Tropical and Temperate CFs was 95 Mg ha-1 and 75.59 Mg ha-1, respectively. Tropical forests exhibited a higher level of biomass (202.14 Mg ha-¹) relative to temperate forests (169.34 Mg ha-¹). The biomass carbon in tropical forests was 1.19 times greater (per hectare) compared to temperate forests. Interestingly, analysis revealed an absence of significant differences in carbon sequestration between the two forests under study with respect to diameter and height class. The study shows that both tropical and temperate forest stands sequester a significant amount of carbon, and appropriate management can yield additional benefits.